Reliable Software for Unreliable Hardware A Cross Layer Perspective - Rehman, Semeen; Shafique, Muhammad; Henkel, Jörg.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes novel software concepts to increase reliability under user-defined constraints. The authors' approach bridges, for the first time, the reliability gap between hardware and software. Readers will learn how to achieve increased soft error resilience on unreliable hardware, while exploiting the inherent error masking characteristics and error (stemming from soft errors, aging, and process variations) mitigations potential at different software layers. · Provides a comprehensive overview of reliability modeling and optimization techniques at different hardware and software levels; · Describes novel optimization techniques for software cross-layer reliability, targeting unreliable hardware.
Introduction -- Background and Related Work -- Cross-Layer Reliability Analysis, Modeling, and Optimization -- Software Program-Level Reliability Modeling and Estimation -- Software Program-Level Reliability Optimization for Dependable Code Generation -- Dependable Code Execution using Reliability-Driven System Software.-Results and Discussion -- Summary and Conclusions.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation